ORIENTALIST SCHOLARSHIP AND EMPIRE: BRITISH INTELLECTUAL ENGAGEMENT WITH INDIA - Gulabray, Vaghela Sumankumar; Patel, Vimal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article explores the tangled and deeply ambivalent relationship between British Orientalist scholarship and the consolidation of imperial power in India from the late eighteenth to the early twentieth century, a relationship defined by a weird mix of genuine intellectual curiosity and the hard-nosed pragmatics of colonial governance. It argues that Orientalism was never a simple, monolithic project of imperial domination as is sometimes claimed; instead, it was an inherently complex, unstable, and often contradictory enterprise, a shifting set of policies and intellectual fashions that adapted to the evolving demands of ruling a vast and bewildering subcontinent. We’ll look at how the early generation of "Orientalists," men like William Jones and H.T. Colebrooke, driven by a blend of Enlightenment rationalism and a romantic fascination with India's ancient past, undertook the monumental task of codifying Indian languages, laws, and religions. Their work, institutionalized through bodies like the Asiatic Society of Bengal, was absolutely indispensable for the East India Company, providing the administrative tools—the legal frameworks, the social taxonomies, the historical narratives—needed to govern a non-European society. Yet, this very act of "knowing the Orient" was fraught with paradox. The British effort to recover and enshrine what they saw as India's "ancient constitution" often resulted in the creation of a rigid, textualized, and distorted version of Indian traditions, particularly in the realm of Hindu law, which was remade in the image of English case law. At the same time, and this is the real kicker, the Orientalist "rediscovery" of India's glorious classical past—the recovery of Sanskrit classics, the deciphering of ancient inscriptions—had the completely unintended consequence of fueling a cultural and intellectual revival, most notably during the Bengal Renaissance. This newfound pride in Indian culture, directly nurtured by Orientalist scholarship, provided the intellectual and ideological ammunition for the emergence of a new middle-class national consciousness, which would eventually challenge the very foundations of the British Raj. So, while Orientalism was undeniably intertwined with the structures of empire, viewing religion and tradition as backward to justify colonial rule, its legacy was profoundly ambivalent, contributing as much to the tools of colonial control as to the seeds of anti-colonial resistance.[1][2][3][4]